2019
DOI: 10.1038/s41386-019-0570-x
|View full text |Cite
|
Sign up to set email alerts
|

Single and repeated ketamine infusions for reduction of suicidal ideation in treatment-resistant depression

Abstract: Repeated administration of subanesthetic intravenous ketamine may prolong the rapid decrease in suicidal ideation (SI) elicited by single infusions. The purpose of this secondary analysis was to evaluate reduction in SI with a single ketamine infusion compared with an active control, and prolonged suppression of SI with repeated and maintenance infusions. Thirty-seven participants with treatment-resistant depression (TRD) and baseline SI first received a single ketamine infusion during a randomized, double-bli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 38 publications
4
52
1
Order By: Relevance
“…One meta-analysis found that ketamine loses its effect in bipolar depression after day 3 or 4. 58 Several RCTs have now looked at repeated infusions of six intravenous infusions over several weeks, 6062 but to date no long-term RCTs exist.…”
Section: Overview Of the Status Of Clinical Trials With Ketamine Andmentioning
confidence: 99%
“…One meta-analysis found that ketamine loses its effect in bipolar depression after day 3 or 4. 58 Several RCTs have now looked at repeated infusions of six intravenous infusions over several weeks, 6062 but to date no long-term RCTs exist.…”
Section: Overview Of the Status Of Clinical Trials With Ketamine Andmentioning
confidence: 99%
“…13 Phillips et al found that patients with a positive response in mood ratings to a single ketamine infusion, which was maximal at 7 days post-infusion, subsequently had sustained reduction in suicidal ideation with repeated weekly infusions. 14 Review of clinical case records has indicated benefits of repeated ketamine infusions in a sizeable proportion of patients. 15 However, there is a shortage of qualitative studies of patients' experiences over time.…”
Section: Ketamine For Treatment Of Depressionmentioning
confidence: 99%
“…Second, the trial includes a novel maintenance strategy for IV ketamine administration that involves sequentially decreasing the frequency of infusions following response. This strategy was shown to effectively maintain antidepressant response and alleviation of suicidal ideation over shortterm follow-up by our group [10,49]. Further support for this approach comes from successful relapse prevention in long-term trials of maintenance administration of intranasal esketamine, an S-enantiomer of racemic ketamine [50].…”
Section: Discussionmentioning
confidence: 99%